gwfish: A simulation software to evaluate parameter-estimation capabilities of gravitational-wave detector networks - Dupletsa, U.; Harms, J.; Banerjee, B.; Branchesi, M.; Goncharov, B.; Maselli, A.; Oliveira, A.C.S.; Ronchini, S.; Tissino, J. (Astronomy and computing, 2023)
An important step in the planning of future gravitational-wave (GW) detectors and of the networks they will form is the estimation of their detection and parameter-estimation capabilities, which is the basis of science-case studies. Several future GW detectors have been proposed or are under development, which might also operate and observe in parallel. These detectors include terrestrial, lunar, and space-borne detectors. In this paper, we present gwfish,11github.com/janosch314/GWFish. a new software to simulate GW detector networks and to calculate measurement uncertainties based on the Fisher-matrix approximation. gwfish models the impact of detector motion on PE and makes it possible to analyze multiband scenarios, i.e., observation of a GW signal by different detectors in different frequency bands. We showcase a few examples for the Einstein Telescope (ET) including the sky-localization of binary neutron stars, and ET’s capability to measure the polarization of GWs.